Determination of the pathophysiological consequences of capture and capture-induced hyperthermia in blesbok (Damaliscus pygargus phillipsi) - Meyer, Leith Carl Rodney (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2016.